Hubungan Mengonsumsi Makanan Kariogenik Terhadap Kejadian Karies Gigi Pada Anak Usia Sekolah Dasar Dengan Resiko Stunting di Sekolah Dasar - saleh, muhammad; Abubakar, Syamsuddin; Wardana, Ridha; Baharuddin (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
ABSTRACT Dental caries is damage to tooth tissue which can be seen by the presence of damage to the tissue, which starts from the surface of the tooth, namely recesses, fissures and interproximal areas that spread to the pulp area. Dental caries can be found in various individuals and can occur on one or more tooth surfaces, and can spread to deeper areas of the tooth, such as from the enamel to the dentin or to the pulp area. The aim of this study was to determine the relationship between consuming cariogenic food and the incidence of dental caries with the target of stunting in elementary school-age children at SD Inpres Unggulan BTN Pemda, Rappocini District, Makassar City. The method used in this study is a quantitative method, namely a survey with a cross-sectional approach. The sample in this study used a purposive sampling technique with a total sample of 50 people. In this study the data came from distributing questionnaires containing questions about the relationship between consuming cariogenic food and the incidence of dental caries in elementary school-age children and questionnaires containing questions about the lifestyle of mothers and children so that they can be said to be at risk of stunting. Children's eating habits and the risk of stunting were measured by filling out a questionnaire form filled out by the students' parents. Caries is measured by looking directly at the condition of the child's teeth using objective examination methods (palpation, percussion, vitality or mobility tests). And for stunting, height and weight checks are carried out to measure student BMI.